Competitive wholesale market of the electric power and power: state and new calls - N. Z. Bakhteeva; L. A. Galimzyanov; Z. V. Shatskikh (Известия высших учебных заведений: Проблемы энергетики)
In article features of functioning of the main segments of the wholesale market of the electric power and power (OREM) are considered. The factors exerting impact on competitiveness of the generation companies come to light. Results of functioning of OREM, since the moment of his full liberalization are analyzed, merits and demerits of the operating market mechanisms reveal.